Study protocol of the HYPER-LIV01 trial: a multicenter phase II, prospective and randomized study comparing simultaneous portal and hepatic vein embolization to portal vein embolization for hypertrophy of the future liver remnant before major hepatectomy for colo-rectal liver metastases - Deshayes, Emmanuel; Piron, Lauranne; Bouvier, Antoine; Lapuyade, Bruno; Lermite, Emilie; Vervueren, Laurent; Laurent, Christophe; Pinaquy, Jean-Baptiste; Chevallier, Patrick; Dohan, Anthony; Rode, Agnès; Sengel, Christian; et al. (BMC cancer, 2020)
Background In patients undergoing major liver resection, portal vein embolization (PVE) has been widely used to induce hypertrophy of the non-embolized liver in order to prevent post-hepatectomy liver failure. PVE is a safe and effective procedure, but does not always lead to sufficient hypertrophy of the future liver remnant (FLR). Hepatic vein(s) embolization has been proposed to improve FLR regeneration when insufficient after PVE. The sequential right hepatic vein embolization (HVE) after right PVE demonstrated an incremental effect on the FLR but it implies two different procedures with no time gain as compared to PVE alone. We have developed the so-called liver venous deprivation (LVD), a combination of PVE and HVE during the same intervention, to optimize the phase of liver preparation before surgery. The main objective of this randomized phase II trial is to compare the percentage of change in FLR volume at 3 weeks after LVD or PVE. Methods Patients eligible to this multicenter prospective randomized phase II study are subjects aged from 18 years old suffering from colo-rectal liver metastases considered as resectable and with non-cirrhotic liver parenchyma. The primary objective is the percentage of change in FLR volume at 3 weeks after LVD or PVE using MRI or CT-Scan. Secondary objectives are assessment of tolerance, post-operative morbidity and mortality, post-hepatectomy liver failure, rate of non-respectability due to insufficient FLR or tumor progression, per-operative difficulties, blood loss, R0 resection rate, post-operative liver volume and overall survival. Objectives of translational research studies are evaluation of pre- and post-operative liver function and determination of biomarkers predictive of liver hypertrophy . Sixty-four patients will be included (randomization ratio 1:1) to detect a difference of 12% at 21 days in FLR volumes between PVE and LVD. Discussion Adding HVE to PVE during the same procedure is an innovative and promising approach that may lead to a rapid and major increase in volume and function of the FLR, thereby increasing the rate of resectable patients and limiting the risk of patient’s drop-out. Trial registration This study was registered on clinicaltrials.gov on 15th February 2019 ( NCT03841305 ).